Synthesis of High χ–Low N Diblock Copolymers by Polymerization‐Induced Self‐Assembly. (4th May 2020) - Jennings, James; Cornel, Erik J.; Derry, Matthew J.; Beattie, Deborah L.; Rymaruk, Matthew J.; Deane, Oliver J.; Ryan, Anthony J.; Armes, Steven P.
Abstract: Polymerization‐induced self‐assembly (PISA) enables the scalable synthesis of functional block copolymer nanoparticles with various morphologies. Herein we exploit this versatile technique to produce so‐called "high χ –low N " diblock copolymers that undergo nanoscale phase separation in the solid state to produce sub‐10 nm surface features. By varying the degree of polymerization of the stabilizer and core‐forming blocks, PISA provides rapid access to a wide range of diblock copolymers, and enables fundamental thermodynamic parameters to be determined. In addition, the pre‐organization of copolymer chains within sterically‐stabilized nanoparticles that occurs during PISA leads to enhanced phase separation relative to that achieved using solution‐cast molecularly‐dissolved copolymer chains. Abstract : Polymerization‐induced self‐assembly enables the scalable synthesis of functional block copolymer nanoparticles with various morphologies. This versatile technique is exploited to prepare so‐called „high χ –low N " diblock copolymers that undergo nanoscale phase separation in the solid state to produce sub‐10 nm domains.